Ordforbindelser i Nudansk Ordbog og andre monolingvale almenordbøger - Becker-Christensen, Christian (LexicoNordica, 2009)
The handling of multiword expressions causes some problems for general dictionaries with regard to the user’s access to them, not only in paper versions, but also in electronic versions. In this article various location and presentation issues are discussed based upon the Danish dictionary Nudansk Ordbog and the larger Den Danske Ordbog, Den Danske Netordbog, the Swedish Nationalencyklopedins Ordbok and the Norwegian Bokmålsordboka considering factors such as production and reception.